The Correlation of Patients' Knowledge About Diabetes Wound Care and Interest in Visiting - Wibowo, Harry Permana; Basri, Basri (Jurnal Keperawatan Priority, 2024)
Diabetes mellitus is a chronic metabolic disease caused by the body's inability to produce insulin according to the body's needs or due to ineffective use of insulin or both. When asked about their understanding of treating gangrene wounds independently, they said they did not fully understand how to treat gangrene wounds. The study aims to determine the correlation between patients' knowledge about diabetic wound care and interest in visiting the surgical clinic at Cut Nyak Dhien Meulaboh Hospital. This type of research used a cross-sectional, with a total sample of 38 respondents. The results showed that most respondents' knowledge was in the good category, namely 22 respondents (57.9%), and the least was in the less good category, 16 respondents (42.1%). The interest in visiting the majority of respondents was in the high class, namely 27 respondents (71.1%), and the least was in the low category, 11 respondents (28.9%). The correlation between the two variables, namely between the respondent's knowledge and interest in visiting the patient, is related to the results of the bivariate test using the Chi-square test, which is 0.00. It can increase their knowledge about diabetic wound care so that they can increase awareness for treating diabetic wounds and regularly re-control the hospital so that the healing process can run well and not cause complications that end in amputation.